An Empirical Study Regarding Radical Innovation, Research and Development Management, and Leadership - Fumihiko Isada; Yuriko Isada (Naše gospodarstvo/Our economy, 2017)
The objective of this research is to empirically compare the management that is most suitable for radical innovation with that needed for incremental innovation. The relationship between the results of research and development and management styles was surveyed using a questionnaire. Respondents included research and development leaders in Japanese manufacturing, with special attention given to the differences between radical innovation and incremental innovation. Results verified, in an integrated way, the management and leadership factors, taking into consideration the differences arising from the object under analysis and the environmental factors.